(untitled) (Engaged Scholar Journal: Community-Engaged Research, Teaching, and Learning, 2019)
This paper invites the reader to consider the power and potential of art for public engagement, and its use in social movement learning and in demanding the world we want now. The authors frame social movements as important sites of scholarship and learning. They emphasize that by applying creative strategies to engage in critical thought about the nature of the world and one’s position in it, artforms have the potential to make essential contributions to social change. Inspired by literature related to critical art-based learning and learning in social movements, the authors explore representations of protest art and public art exhibitions. They contextualize their writing with stories of mobile art exhibits in Sao Paulo, the ‘maple spring’ in Montreal (Tiotia:ke in the language of the Kanien’kehá:ka), and anti–Bill C-51 protests in Lekwungen territory (Victoria, British Columbia). They present and reflect on their own experiences of using art as engagement and as a representation of voice in public demonstrations.